The placebo effect of ankle taping in ankle instability - Sawkins, K.; Refshauge, K.; Kilbreath, S.; Raymond, J. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Recurrence of ankle sprains is common among athletes. Although ankle taping reduces the risk of injury, the mechanism underlying its effectiveness remains unclear. Anecdotal reports suggest a role of the belief among athletes that taping will protect them from injury. That is, taping may have a placebo effect. The purpose of the present study was to determine whether there was a placebo effect with ankle taping in individuals with ankle instability.